Organ donor pancreases for the study of human islet cell histology and pathophysiology: a precious and valuable resource - Marchetti, Piero (Diabetologia, 2018)
Direct in vivo assessment of pancreatic islet-cells for the study of the pathophysiology of diabetes in humans is hampered by anatomical and technological hurdles. To date, most of the information that has been generated is derived from histological studies performed on pancreatic tissue from autopsy, surgery, in vivo biopsy or organ donation. Each approach has its advantages and disadvantages (as summarised in this commentary); however, in this edition of Diabetologia, Kusmartseva et al (10.1007/s00125-017-4494-x) provide further evidence to support the use of organ donor pancreases for the study of human diabetes. They show that length of terminal hospitalisation of organ donors prior to death does not seem to influence the frequency of inflammatory cells infiltrating the pancreas and the replication of beta cells. These findings are reassuring, demonstrating the reliability of this precious and valuable resource for human islet cells research.